Second Metabolite Composition, Antioxidative, Tyrosinase Inhibitory, Antibacterial and Anticancer Activity of Balanophora laxiflora Extract - Hang, Tran Thi; Quyen, Tran Thi; Huy, Nguyen Quang; Hoa, Le Thi Phuong (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Balanophora laxiflora extract contains various compounds including terpenoids, phenolics, and flavonoids. Ethyl acetate fraction of B. laxiflora has high content of phenolic compounds  (608.21 mg GAE/g), highly correlated with its antioxidant activity including 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging capacity (IC 50 value of 22.81 µg/mL) and reducing power (2.33), which is comparable to that of ascorbic acid and quecertin. This fraction shows strong tyrosinase inhibitory activity with IC 50 value of 7.9 µg/mL and mild inhibitory activity against Gram-positive and Gram-negative strains at the concentration of 20 mg/mL, stronger than those of other fractions. Ethyl acetate fraction also exhibited cytotoxicity against human lung carcinoma (LU-1) cell line. n-Hexane fraction shows stronger activity on epidermal carcinoma (KB) cell lines (IC 50 = 3.45 µg/mL). Median lethal dose (LD 50 ) of B. laxiflora methanolic crude extract on experimental mice is 10.64 g/kg body mass. The results suggest new pharmacological use of B. laxiflora especially in depigmentation, cancer treatment and further characterization of bioactive constituents and biological activities of ethyl acetate and n-hexane fraction. Keywords: Balanophora laxiflora , antioxidative activity, tyrosinase inhibition, antibacterial activity, anticancer activity